2013 8th International Symposium on Image and Signal Processing and Analysis (ISPA) 2013
DOI: 10.1109/ispa.2013.6703766
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hammerstein model using cubic splines and FIR filtering

Abstract: Nonlinear models are exploited in the field of digital audio systems for modelling most of real-world devices that show a nonlinear behaviour. Among nonlinear models, Hammerstein systems are realized through a static nonlinearity cascaded with a linear filter. In this paper, the Hammerstein coefficients are estimated using an adaptive Catmull-Rom cubic spline for the static nonlinearity and an adaptive FIR filter for the dynamic linear system also introducing a pre-processing for the time delay estimation. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…It is useful to note that, having chosen as input a signal x(t) for which the ω 1 and ω 2 angular frequency components have the same amplitude R, their role will be interchangeable, and the coefficients of the respective harmonics will be equal to each other. Consequently, to avoid linear dependence between equations of the system, the function g(t) related only to one of the two angular frequencies has been inserted in the vector (13). The matrix [A I MD ] therefore plays, in the case that the input signal is a double exponential swept-sine signal, a role similar to that played by [A c ] −1 T in the case of the single exponential swept-sine signal [23].…”
Section: Derivation Of the Estimation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…It is useful to note that, having chosen as input a signal x(t) for which the ω 1 and ω 2 angular frequency components have the same amplitude R, their role will be interchangeable, and the coefficients of the respective harmonics will be equal to each other. Consequently, to avoid linear dependence between equations of the system, the function g(t) related only to one of the two angular frequencies has been inserted in the vector (13). The matrix [A I MD ] therefore plays, in the case that the input signal is a double exponential swept-sine signal, a role similar to that played by [A c ] −1 T in the case of the single exponential swept-sine signal [23].…”
Section: Derivation Of the Estimation Proceduresmentioning
confidence: 99%
“…Even if the obtained model is highly accurate, a complete knowledge of the physical system is not always possible. For this reason the grey and black box approaches have been developed, which respectively require only a partial knowledge of the system, or only the knowledge of input and output signals [13], [14], [15]. Grey box approaches use the input/output (I/O) relationship to identify the system and then the model is improved using the block diagram of the circuit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The filters find application in speech [1], audio [2,3], telecommunication [4], image processing [1], biological system modeling [5], and many other fields. The LIP class includes truncated Volterra filters [1], still actively studied and used in applications [6][7][8][9][10], but also Wiener nonlinear filters [1], Hammerstein filters [1,[11][12][13][14], memory and generalized memory polynomial filters [15,16], filters based on functional expansions of the input samples, as functional link artificial neural networks (FLANN) [17][18][19][20] and radial basis function networks [21]. A review of finite-memory LIP nonlinear filters can be found in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among LIP filters, the most popular are the truncated Volterra filters [1], still actively studied and used in applications [2, 3,4,5,6,7,8,9]. Other elements of the class include particular cases of Volterra filters, as the Hammerstein filters [1, 10,11,12,13], and modified forms of Volterra filters, as memory and generalized memory polynomial filters [14,15]. Filters based on functional expansions of the input samples, as functional link artificial neural networks (FLANN) [16] and radial basis function networks [17], also belong to the LIP class.…”
Section: Introductionmentioning
confidence: 99%